TARGET COSTING BASED ON THE ACTIVITY-BASED COSTING METHOD AND A MODEL PROPOSAL - Pazarceviren, Selim Yuksel; Celayir, Duygu (European Scientific Journal, ESJ, 2014)
Globalization arisen with the fast transformations in economy and technology, is also accompanied consequential changes in the competition environment of the businesses. Global competititon environment obligated businesses to reach three important objectives at the same time and at the highest level. Businesses have had to design and produce high-quality, low-cost products to meet customer requests and expectations as soon as possible. In this environment, conventional cost methods and cost-plus pricing strategies have became insufficient, therefore new cost management methods have been developed. One of these methods is Target Costing method. Target Costing is a method that aims to manage the costs before they realized and to realize target profit at a level of realizable cost without making any concessions on quality. With regard to realizing these objectives, accuracy of the managerial decisions have to be increased. However, conventional cost methods do not secure the accuracy of cost information and they are not beneficial for the prediction and decision mechanisms of the executives. Activity-Based Costing method that is based on activity-based information methods, is appeared in the 1980s. The method has eliminated insufficiencies of conventional methods due to its ability to provide more accurate cost information. Activity-based approach that is started with the activity-based costing also has been realized in budgeting. Thereby, functional-based conventional costing has gave way to activity-based costing. Both the activity-based costing and activity-based budgeting have been became tools that can be utilised effectively for determining and estimating target costs. Our study states that target costing method can be realized in conjuction with the Activitybased costing method for ensuring the desired efficiency of the target costing method. Furthermore, a target cost model based upon activity-based costing and activity-based budgeting, has been developed.